Genetics of two μ opioid receptor gene (OPRM1) exon I polymorphisms: population studies, and allele frequencies in alcohol- and drug-dependent subjects - Gelernter, J; Kranzler, H; Cubells, J (Molecular psychiatry, 1999)
The gene encoding the μ opioid receptor, OPRM1, contains at least two polymorphisms affecting protein sequence in exon 1, Ala6Val and Asp40Asn. In previous studies, each variant has been reported to be associated with some form of drug dependence. Although past reports have not been consistent, they have also not considered comparable populations. The goals of the present study were to delineate allele and haplotype frequencies of these variants in a range of populations, and in drug- or alcohol-dependent subjects deriving from some of those populations. We developed new PCR-RFLP methods to detect both of these polymorphisms and studied them in control and substance-dependent populations of African American (AA), European American (EA) and Hispanic origin, and in a series of populations differing in geographic origin (Japanese, Ethiopians, Bedouins, and Ashkenazi Jews), 891 subjects overall. We designed primers flanking the DNA segment containing both polymorphisms, each primer creating a different artificial restriction site, such that a single PCR reaction can be completed, then divided, and the PCR product digested with either of two enzymes to reveal both polymorphisms. We found that allele frequencies for both polymorphic systems were significantly different between AA and EA subjects, and there was significant heterogeneity among the more extensive set of populations. Furthermore, there were no significant differences in allele frequency by diagnosis; that is, neither polymorphism appears to be a direct risk factor for substance dependence. Finally, we demonstrated linkage disequilibrium between the two exon 1 markers, and a previously described short tandem repeat (STR) marker.